Impact of ranolazine on ventricular arrhythmias – A systematic review. Issue 2 (12th January 2018) - Bazoukis, George; Tse, Gary; Letsas, Konstantinos P.; Thomopoulos, Costas; Naka, Katerina K.; Korantzopoulos, Panagiotis; Bazoukis, Xenophon; Michelongona, Paschalia; Papadatos, Stamatis S.; Vlachos, Konstantinos; Liu, Tong; Efremidis, Michael; et al.
Abstract: Ranolazine is a new medication for the treatment of refractory angina. However, except its anti‐anginal properties, it has been found to act as an anti‐arrhythmic. The aim of our systematic review is to present the existing data about the impact of ranolazine in ventricular arrhythmias. We searched MEDLINE and Cochrane databases as well clinicaltrials.gov until September 1, 2017 to find all studies (clinical trials, observational studies, case reports/series) reported data about the impact of ranolazine in ventricular arrhythmias. Our search revealed 14 studies (3 clinical trials, 2 observational studies, 8 case reports, 1 case series). These data reported a beneficial impact of ranolazine in ventricular tachycardia/fibrillation, premature ventricular beats, and ICD interventions in different clinical settings. The existing data highlight the anti‐arrhythmic properties of ranolazine in ventricular arrhythmias.